2016
DOI: 10.2147/dhps.s95535
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility, safety, and efficacy of pregabalin in the treatment of fibromyalgia

Abstract: Fibromyalgia is a chronic debilitating medical syndrome with limited therapeutic options. Pregabalin, an anticonvulsant and α-2-Δ subunit receptor ligand, is one of the anchor drugs approved by the US Food and Drug Administration for the treatment of fibromyalgia. The drug has shown clinically meaningful benefits across multiple symptom domains of fibromyalgia. Efficacy of pregabalin in fibromyalgia pain has been evaluated in at least five high-quality randomized trials, two long-term extension studies, a meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
0
17
0
2
Order By: Relevance
“…However, with pregabalin treatment, subjects developed tolerance to these TEAEs. 15 In the multiple-ascending-dose study, somnolence or dizziness resolved or improved within 4-5 days, suggesting that tolerance developed to these CNS TEAEs. Asymptomatic elevation of hepatic transaminase levels was reported in 1 subject receiving mirogabalin 10 mg BID in the multiple-ascending-dose study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, with pregabalin treatment, subjects developed tolerance to these TEAEs. 15 In the multiple-ascending-dose study, somnolence or dizziness resolved or improved within 4-5 days, suggesting that tolerance developed to these CNS TEAEs. Asymptomatic elevation of hepatic transaminase levels was reported in 1 subject receiving mirogabalin 10 mg BID in the multiple-ascending-dose study.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it was not unexpected that, in both the single‐ and multiple‐ascending‐dose studies, dizziness and somnolence were among the most commonly reported TEAEs. However, with pregabalin treatment, subjects developed tolerance to these TEAEs . In the multiple‐ascending‐dose study, somnolence or dizziness resolved or improved within 4‐5 days, suggesting that tolerance developed to these CNS TEAEs.…”
Section: Discussionmentioning
confidence: 99%
“…ECG monitoring should be recommended for the patients undergoing pregabalin therapy, if necessary. Furthermore, pregabalin itself, which is commenced as an auxiliary medication for the treatment of epilepsy (Baldwin et al., ; Bhusal, Diomampo, & Magrey, ) can be the cause of next syncope by prolonging the QT interval. Prolonged QT interval should be excluded during epileptic attacks in the patients receiving pregabalin for epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged QT interval should be excluded during epileptic attacks in the patients receiving pregabalin for epilepsy. Pregabalin is a gamma‐aminobutyric acid analogue it acts by blocking L‐type calcium canals resulting in decreased level of neurotransmitters such as substance p, norepinephrine, and glutamate (Baldwin et al., ; Bhusal et al., ). Most common side effects of pregabalin include dizziness, sensation of numbness and blurred vision.…”
Section: Discussionmentioning
confidence: 99%
“…With PG, many patients manage to obtain significant benefits regarding pain control, quality of life, and especially in sleep improvement. Moreover, the side effects, even though they are somewhat common, are normally mild and well tolerated in the long term, and may also be monitored in primary care 17 . Based on the above, a discussion on the relationship between PG and sleep in cases of FM becomes valid, so that the doctor may have the best possible grounding in establishing his or her conduct for the cases considered.…”
Section: Review Articlementioning
confidence: 99%